Phenotypes of intermediate forms of Fasciola hepatica and F. gigantica in buffaloes from Central Punjab, Pakistan. Issue 4 (December 2014) - Afshan, K.; Valero, M.A.; Qayyum, M.; Peixoto, R.V.; Magraner, A.; Mas-Coma, S.
Abstract Fascioliasis is an important food-borne parasitic disease caused by the two trematode species, Fasciola hepatica and Fasciola gigantica. The phenotypic features of fasciolid adults and eggs infecting buffaloes inhabiting the Central Punjab area, Pakistan, have been studied to characterize fasciolid populations involved. Morphometric analyses were made with a computer image analysis system (CIAS) applied on the basis of standardized measurements. Since it is the first study of this kind undertaken in Pakistan, the results are compared to pure fasciolid populations: (a) F. hepatica from the European Mediterranean area; and (b) F. gigantica from Burkina Faso; i.e. geographical areas where both species do not co-exist. Only parasites obtained from bovines were used. The multivariate analysis showed that the characteristics, including egg morphometrics, of fasciolids from Central Punjab, Pakistan, are between F. hepatica and F. gigantica standard populations. Similarly, the morphometric measurements of fasciolid eggs from Central Punjab are also between F. hepatica and F. gigantica standard populations. These results demonstrate the existence of fasciolid intermediate forms in endemic areas in Pakistan.